“. . . ultimately alone and walking around in your own private universe”: Metatheatre and Metaphysics in Three Plays by Enda Walsh - Wallace, Clare (Hungarian Journal of English and American Studies, 2020)
This paper analyzes Enda Walsh’s three major new plays between 2006 and 2014: The Walworth Farce (2006), Penelope (2010), and Ballyturk (2014). In this period Walsh’s work shifts from being primarily linguistically oriented to becoming much more attentive to the shape and modalities of performance. Bedbound, Misterman, The Small Things, and The Walworth Farce share a focus on aberrant and confining narrative performance, but a fault line lies between The Small Things and The Walworth Farce. The frenetic pace and surreal tone of the plays remains constant; however, there is a crucial difference in emphasis between carrying on and carrying out such a performance. In this new phase in Walsh’s dramaturgy an elaboration of ritualized, repetitive, and carefully choreographed action in symbolically charged spaces is accompanied by the fragmentation of mimetic and diegetic readability. At the heart of this work is a fundamental set of anxieties. The Walworth Farce, Penelope, and Ballyturk, each in different ways, are plays about performance and performativity vis à vis creativity and death. (CW)